Root Diversity in Characteristic Plant Species of Manu Swamp : a Sub-tropical Fresh-water Swamp at Rishikesh (Dehra Dun) - Ghildiyal, J. C.; Srivastava, M. M. (Indian Forester, 2007)
Manu Swamp, a sub-tropical fresh-water swamp lies in Compartment 4 of Barkot Forest Range, Eastern Doon Forest Division in the foothills on Rishikesh-Hardwar road (30Â° 07'N latitude 78Â°19' E longitude). The root system of characteristic plant species was observed selecting the representative of each plant community of Manu Swamp. All the representatives of different communities in Manu Swamp showed the phenomenon of heterorrhizae. The heterorrhizae represented was of typical type except in Adhatoda zeylanica where a typical heterrorrhizae was there, due to its basic terrestrial habit. In most of these plants brachyrrhizae were poorly developed, due to availability of water in plenty. Macrorrhizae were prominent in all species. The shallow root system, the presence of stilts roots in Trewia nudiflora, peg root like structures in Bischofia javanica, the surface roots running horizontally in Trewia nudiflora and Bischofia javanica and the presence of root buttresses in all trees show the adaptability of these plants to water-logged conditions of fresh-water swamp.The interwoven nature of root system and presence of underground rhizome in most of herbs and shrubs present in swamp proper, played important role in binding of soil particles in water-logged soil.